Long-term effects of additional insulation of building façades in Sweden: Towards a holistic approach. Issue 2 (13th August 2019) - Tunefalk, Martin; Legner, Mattias; Leijonhufvud, Gustaf
Abstract : Purpose: The purpose of this paper is to evaluate long-term effects of previous policies for energy efficiency on energy performance and heritage values. A further ambition is to better understand the relationship between energy and preservation by exploring a quantitative method of combining energy performance data with official heritage designation. Design/methodology/approach: The study is based on a quantitative analysis of energy performance, completed additional insulations, and official heritage classification for individual buildings. Data have been collected and analysed for a sample consisting of 289 multi-family buildings heated with district heating and constructed 1940–1949 in an urban area in Stockholm, Sweden. Findings: The data exhibit a significant correlation between the studied features. The study further shows that additional insulation has been installed in roughly half of the buildings. The large majority of them were carried out in the national programme for home improvement called ROT. Research limitations/implications: The findings indicate that previous policies for energy efficiency had an important effect on energy performance and heritage values in the studied area. They continue to affect urban planning and building permit administration today. Research of the physics of individual buildings would be needed in order to determine the reason for differences in the sample. Originality/value: By presenting a novel method, the study provides a useful tool for policy makers to bridge the gap between issues of energy and preservation and adopt a more holistic approach towards a sustainable built environment.